EFL Learners’ Perception of Non-Native Speakers' Accent and Identity in English Education Study Program Universitas Negeri Makassar - Afra, Firyal Talietha; Noni, Nurdin; Muhayyang, Maemuna (Program Studi Pendidikan Bahasa Inggris FBS UNM, 2024)
The objectives of this study were to explore EFL learners’ perception of the non-native speaker accent and identity and to explore the EFL learner’s perception of the relationship between accent prefaces and identity in the English Education Study Program, Universitas Negeri Makassar. The research utilized a descriptive qualitative approach, specifically employing a case study method. The subject of this research was students at Universitas Negeri Makassar. The researchers used interviews as instruments to collect the data in this research. Based on the findings of the research, the results show EFL learners’ perception of the non-native speaker accent and identity and EFL learner’s perception of the relationship between accent prefaces and identity, namely (1) EFL learners predominantly employ American English pronunciation over Received Pronunciation and (2) the relationship between English accent preferences and identity is a complex interplay of social, cultural, and individual factors, encompassing notions of social class, regional identity, cultural heritage, and personal agency. The study contributes to the growing literature on English and accent variation, offering insights that can inform language policy and curriculum development in diverse educational contexts.